Development of an automated unit testing tool for java program. - Zamli, Kamal Zuhairi; Mat Isa, Nor Ashidi (Universiti Sains Malaysia, 2009)
Software testing relates to the process of executing a program or system with the intent of finding errors. Covering as much as 25 to 35 percent of the development costs and resources, software testing is an integral part of the software development lifecycle.